Faktor Yang Mempengaruhi Kejadian BBLR (Berat Badan Lahir Rendah) Di Ruang Perawatan Intensif Neonatus RSUD DR Moewardi Di Surakarta - Ayu Rosida Setiati; Sunarsih Rahayu (Poltekkes Kemenkes Surakarta, 2017)
Abstract: Low Birth Weight, Age, Hypertension. Weight is one health indicator of the newborn. In basic, infants with low birth weight of less than 2500 grams have a greater risk of health problems which cause by many factor like hypertension, anemia, asthma, a history of low birth weight, birth spacing, parity, antepartum haemorrhage, rupture prematures, and placenta previa. The purpose of this study to determine the factors that influence the incidence of low birth weight in neonatal intensive care units of DR Moewardi Hospital. This study design was retrospective descriptive analytic approach in low birth weight infants in the neonatal intensive care unit of DR Moewardi Hospital in January to March 2016. The sampling technique using total sampling. The inclusion criteria low birth weight infants in the neonatal intensive care DR. Moewardi Hospital, mothers who gave birth low birth weight in DR Moewardi Hospital, low birth weight babies referrals from outside hospitals DR Moewardi accompanied by her mother who participated to DR Moewardi Hospital. Exclusion criteria mothers with low birth weight babies and low birth weight infants who died. Analysis data with frequency distribution and bivariate using Chi Square test. The age (p=0.021), hypertension (p=0.049), parity (p=0.024), antepartum haemorrhage (p=0.049), eclampsia (p=0,049), rupture prematures (p=0.031) was associated with low birth weight. Anemia (p=0.737) bronchial asthma (p=0.362), a history of low birth weight (p=0.554), birth spacing (p=0.680), placenta previa (p=0.258) was not associated with low birth weight. Age, hypertension, parity, antepartum haemorrhage, eclampsia and rupture prematures associated with low birth weight